A duodenal gastrointestinal stromal tumor with a large central area of fluid and gas due to fistulization into the duodenal lumen, mimicking a large duodenal diverticulum - Okasha, Hussein Hassan (Endosc Ultrasound, 2015)
Gastrointestinal stromal tumors (GISTs) can occur anywhere along the gastrointestinal tract especially the stomach and upper small bowel. They are usually solid, but cystic degeneration, necrosis, and focal hemorrhage have been described in larger tumors leading to central necrotic cavitation. The most sensitive marker of GIST is CD117 (c-kit). In computed tomography (CT) scan, it is often difficult to decide the origin of the primary tumor, especially in large GISTs. We report an incidental case of a large duodenal GIST fistulizing into the second part of the duodenum with a large amount of fluid and gas inside, mistaken for a cystic pancreatic neoplasm by CT and mistaken for a duodenal diverticulum by endoscopic ultrasound.